2018
DOI: 10.3390/ijms19103125
|View full text |Cite
|
Sign up to set email alerts
|

The Role of AMPK in the Regulation of Skeletal Muscle Size, Hypertrophy, and Regeneration

Abstract: AMPK (5’-adenosine monophosphate-activated protein kinase) is heavily involved in skeletal muscle metabolic control through its regulation of many downstream targets. Because of their effects on anabolic and catabolic cellular processes, AMPK plays an important role in the control of skeletal muscle development and growth. In this review, the effects of AMPK signaling, and those of its upstream activator, liver kinase B1 (LKB1), on skeletal muscle growth and atrophy are reviewed. The effect of AMPK activity on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
128
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(150 citation statements)
references
References 140 publications
(204 reference statements)
4
128
0
Order By: Relevance
“…Indeed, in the present study, we found that daily administration of B-3 to rats for a prolonged period tended to increase muscle mass and activate AMPK, a well-known master metabolic regulator, in the soleus [22,23]. Furthermore, the gene expression of PGC-1α and CCO was higher in the B-3 administration group than in the control group.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Indeed, in the present study, we found that daily administration of B-3 to rats for a prolonged period tended to increase muscle mass and activate AMPK, a well-known master metabolic regulator, in the soleus [22,23]. Furthermore, the gene expression of PGC-1α and CCO was higher in the B-3 administration group than in the control group.…”
Section: Discussionsupporting
confidence: 52%
“…In general, AMPK is well known to inhibit protein synthesis through the suppression of the mTOR, a critical regulator of anabolic pathways [22,23], which indicates that the co-activation of both anabolic and catabolic pathways does not occur in the skeletal muscle at the same time. However, we observed the co-activation of Akt and AMPK in response to B-3HK by western blotting analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The atrophy is executed mainly by regulated proteolysis of contractile proteins through the proteasome but also autophagy‐lysosomal breakdown of other redundant myofibre constituents occur in parallel . The signalling pathways governing contractile protein breakdown is normally active and balanced by stimuli to increase myosins to enlarge myofibre size and muscle mass . Originating from theory that the DNA of a nucleus can support but a limited cellular volume and that this relationship sets a ceiling for growth (; myonuclear domain, MND), major alteration in fibre size should be accompanied by either a reduction of total number of myonuclei or the recruitment and incorporation of de novo formed myonuclei deriving from the regional stem cell niche, ie, Satellite cell (SC) niche .…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] The signalling pathways governing contractile protein breakdown is normally active and balanced by stimuli to increase myosins to enlarge myofibre size and muscle mass. [30][31][32][33][34][35][36] Originating from theory that the DNA of a nucleus can support but a limited cellular volume and that this relationship sets a ceiling for growth (37)(38)(39) ; myonuclear domain, MND), major alteration in fibre size should be accompanied by either a reduction of total number of myonuclei or the recruitment and incorporation of de novo formed myonuclei deriving from the regional stem cell niche, ie, Satellite cell (SC) niche. [40][41][42][43][44] As currently debated, more recent data suggest that both significant atrophy and hypertrophy can occur without changes to number of myonuclei 39,41 or replenishment of myonuclei from the SC cell niche.…”
mentioning
confidence: 99%